Durasi, Frekuensi, dan Intensitas pada Remaja dalam Bahasa Melayu Dialek Tanjungbalai Asahan - Maulida, Dini Eka; Syarfina, T (Universitas Muhammadiyah Jember, 2026)
This study aims to describe the acoustic phonetic characteristics in terms of duration, frequency, and intensity of speech produced by adolescent native speakers of the Tanjungbalai Asahan Malay Dialect (BMDTA) based on gender differences. This research employed a quantitative experimental method with an instrumental approach. The research data consisted of recorded declarative utterances of the sentence ‘kucingtu talenggek kaReto’ (the cat was hit by a motorcycle) produced by three informants, namely two female adolescents and one male adolescent aged 17-18 years who are native speakers of BMDTA. Data were collected through recording techniques and analyzed using Praat software to obtain duration, frequency, and intensity values. Data validity was tested through triangulation techniques and repeated measurements. The results showed that female speakers tended to produce longer utterance durations than male speakers. Speaker RP II produced the longest duration of 2.897 seconds, while speaker RL produced the shortest duration of 2.031 seconds. In terms of frequency, female speakers demonstrated higher maximum frequency values, with the highest frequency found in RP I at 326.5 Hz, while the lowest maximum frequency was found in RL at 174.9 Hz. Regarding intensity, RP II showed the highest maximum intensity at 80.5 dB; however, the findings indicated that intensity is not entirely determined by gender. These acoustic characteristic differences are influenced by physiological, social, and speech habit factors of the speakers.